The biocompatibility of Achyrocline satureioides plant extract over human gingival fibroblasts (Research, Society and Development, 2021)
Objective: Achyrocline satureioides “A.satureioides” is a subshrub, widely distributed in South America because of its medicinal properties. Although it is widely used in folk medicine, there is still no approval for its therapeutic use, and its biocompatibility is little explored.  This study aimed to evaluate its cytotoxicity and genotoxicity over human gingival fibroblasts (FMM-1). Methodology: Ten different concentration of the glycolic extract of A.satureioides were tested for 5min and 24h of contact with the cells to evaluate its cytotoxicity using the MTT colorimetric assay and to evaluate its genotoxicity using the micronucleus assay. Data were analyzed with one-way ANOVA and Tukey test with a significance level (α=0.05). Results: All tested concentrations of the extract presented cell viability more than 70% and has no significant difference of the control group after 5min and 24h. However, for 5min the 100 mg/mL was cytotoxic and for 24h the 1.56 mg/mL stimulated cell proliferation. For genotoxicity analysis, only the concentration 6.25 mg/mL showed results similar to the control of cell culture in the micronucleus count after 5min and 24h. Conclusions: The glycolic extract of A.satureioides doesn’t have cytotoxic and genotoxic effects in concentrations up to 6.25 mg/mL, but in high concentrations it is considered genotoxic.